Kinetic modelling of gas-phase reactions of polyethylene-derived pyrolysis products in steam gasification - Bengtsson, Hanna (My University, 2018)
Today, only 15% of the plastic waste in Europe is recycled. However, the existing recycling processes used, cannot preserve the quality of the material. The main production of plastic products is based on fossil resources and to ensure future assets, and to reduced environmental impact, new technology for recycling is demanded. Gasification of plastic has so far been utilized for production of fuels, and the next step is the possibility of production of hydrocarbon monomers. Gasification of hydrocarbon polymers includes an initial step of pyrolysis, followed by secondary gas-phase reactions of the volatile pyrolysis products and the gasifying agent. In this Master’s Thesis, a kinetic model of the secondary gas-phase reactions of polyethylene steam gasification at 700-800°C, is formulated. Based on existing hydrocarbon thermodynamic and kinetic mechanisms, a plug flow model is simulated in ANSYS Chemkin-Pro, with an input of polyethylene-derived pyrolysis products obtained from earlier published literature. From the simulated results it is concluded, that the provided input temperature profiles and sets of reactant input compositions, have low influence on the obtained results. Instead, the residence time shows the highest influence of the progress of product specie concentrations, where the largest increase occurs within 20 ms. Study of reaction pathways for the applied conditions, show that in relation to ethylene, the simulated results are similar to literature of pyrolysis and combustion processes. In relation to existing experimental data of polyethylene steam gasification, from the gasification unit in Chalmers Power Central, the simulated yields are overall higher for the hydrocarbon species, while the products of the water-gas shift reaction are underestimated. The formulated model can further be used for explicit examination of specific mechanisms related to the process of steam gasification of hydrocarbon polymers. The model set-up provides the possibility to study different conditions regarding temperature, pressure, residence time and reactant input composition.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering